Double‐Strand DNA Breaks Induced by Paracyclophane Gold(I) Complexes. Issue 26 (20th March 2017) - Bestgen, Sebastian; Seidl, Carmen; Wiesner, Thomas; Zimmer, Andreas; Falk, Martina; Köberle, Beate; Austeri, Martina; Paradies, Jan; Bräse, Stefan; Schepers, Ute; Roesky, Peter W.
Abstract: Gold(I) complexes of ClickPhos [2.2]paracyclophane ligands were synthesized in excellent yields and fully characterized by spectroscopic methods as well as X‐ray crystallography. The complexes exhibit a rigid ligand backbone and a triazolyl moiety and were systematically studied with respect to their cytotoxic properties. In combination with the ionic complex [(GemPhos)Au(tht)][ClO4 ] (tht=tetrahydrothiophene), in which the gold(I) atom exhibits a distorted trigonal coordination sphere of two phosphines and a labile tht ligand, their efficiency in cytotoxicity was investigated in HeLa, MCF7, and HCT116 cells as well as in a zebrafish model. Their cytotoxicity and their mechanisms of action are different and involve apoptosis, necrosis, and DNA damage. The compounds presented herein are potent metal‐based cytostatics displaying LD50 values from 3.5–38 μm in different tumor cell lines and induce double‐strand DNA breaks (DSB) as shown by H2AX phosphorylation (γH2AX) at foci of DSBs. Abstract : Breaking up DNA : Gold(I) complexes of ClickPhos [2.2]paracyclophane ligands were synthesized. Their efficiency in cytotoxicity was investigated in HeLa, MCF7, and HCT116 cells as well in a zebrafish model. The compounds presented herein are potent metal‐based cytostatics displaying LD50 values from 3.5–38 μm in different tumor cell lines and induce DNA breaks (DSBs) as shown by H2AX phosphorylation (γH2AX) at foci of DSBs.